Proceedings of the 2nd International Conference on Virtual Execution Environments 2006
DOI: 10.1145/1134760.1134776
|View full text |Cite
|
Sign up to set email alerts
|

Relative factors in performance analysis of Java virtual machines

Abstract: Many new Java runtime optimizations report relatively small, single-digit performance improvements. On modern virtual and actual hardware, however, the performance impact of an optimization can be influenced by a variety of factors in the underlying systems. Using a case study of a new garbage collection optimization in two different Java virtual machines, we show the relative effects of issues that must be taken into consideration when claiming an improvement. We examine the specific and overall performance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Since SableVM did not have an optimizing compiler, it was hard for Gagnon to perform a detailed performance evaluation of this design. More recently Gu, Verbrugge and Gagnon [13] set out to compare the performance of this layout in Jikes RVM but concluded that it was difficult to accurately evaluate such design choices in the context of a complex, non-deterministic JVM. Dayong Gu generously made available to us his port to Jikes RVM of the SableVM bidirectional object model, which we forwardported, tuned, and used in our evaluation of the bidirectional object model reported here.…”
Section: Related Workmentioning
confidence: 99%
“…Since SableVM did not have an optimizing compiler, it was hard for Gagnon to perform a detailed performance evaluation of this design. More recently Gu, Verbrugge and Gagnon [13] set out to compare the performance of this layout in Jikes RVM but concluded that it was difficult to accurately evaluate such design choices in the context of a complex, non-deterministic JVM. Dayong Gu generously made available to us his port to Jikes RVM of the SableVM bidirectional object model, which we forwardported, tuned, and used in our evaluation of the bidirectional object model reported here.…”
Section: Related Workmentioning
confidence: 99%
“…Hardware information obtained from hardware counters can also be used to improve static compilers; Cavazos et al use performance counters to as a means of determining good compiler optimization settings [10]. Other works based on hardware event information can be found in [32,38,18]. Many software applications and libraries are available to access these counters, including VTune, PMAPI, PCL and PAPI [7].…”
Section: Related Workmentioning
confidence: 99%
“…Although this is only one of many possible choices, Gu and Verbrugge have previously shown the importance of "L1 instruction cache miss" on JVM performance [18]. Of course the L1 I-cache is a global resource, subject to potential pollution by other processes.…”
Section: Hardware Performance Datamentioning
confidence: 99%
“…11 A ratio of 1 indicates no effect on performance, a ratio of 10 Soot is unable to read in classfiles that include jsr instructions with no matching ret. This is not a limitation of Dava itself but we marked it as having crashed on the CB2JI obfuscation because of this.…”
Section: Impact Of Obfuscations On Performancementioning
confidence: 99%
“…As shown by recent empirical studies by Gu et al [9,10], small variations in code layout can lead to relatively large performance differences in Java (on the order of 5-10%). Thus, we can expect some performance differences between the original and obfuscated code just because the obfuscated code leads to different code layouts.…”
Section: Impact Of Obfuscations On Performancementioning
confidence: 99%